2022
DOI: 10.1111/hdi.13014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, practices, and outcomes in a Belgian cohort of incident home hemodialysis patients: A 6‐year experience

Abstract: Background: Home hemodialysis (HHD) remains underused in patients with kidney failure. Current literature on HHD mostly originates from non-European countries, making generalization difficult. The present study describes patients' profile and practice patterns from a Belgian HHD center, and assesses patient and technique survival and complications associated with HHD.Methods: We analyzed data from all our incident patients during a 6-year period. The patient's characteristics were summarized using descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Although the KDOQI Guideline for Vascular Access: 2019 Update still does not consider central venous catheters (CVCs) as the preferred vascular access for HD 2 , the real proportion is much higher, particularly in older patients and patients with diabetes, and > 60% of patients’ first HD access is CVC 3 , 4 . In addition, > 50% of the patients on home HD have a CVC as their initial vascular access 5 , 6 . Moreover, recent studies have found that CVCs are not directly associated with mortality 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the KDOQI Guideline for Vascular Access: 2019 Update still does not consider central venous catheters (CVCs) as the preferred vascular access for HD 2 , the real proportion is much higher, particularly in older patients and patients with diabetes, and > 60% of patients’ first HD access is CVC 3 , 4 . In addition, > 50% of the patients on home HD have a CVC as their initial vascular access 5 , 6 . Moreover, recent studies have found that CVCs are not directly associated with mortality 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%